An assessment of the influence of personal branding on financing entrepreneurial ventures. Issue 2 (February 2019) - ElMassah, Suzanna; Michael, Ian; James, Reynold; Ghimpu, Ionica
Abstract: This research explores the influence of an entrepreneur's personal brand in attracting capital, by examining the validity of the Entrepreneurial Brand Personality Equity (EBPE) model of Balakrishnan and Michael (2011). Its particular concern is whether investors provide funding to an entrepreneur's idea, or, to the entrepreneur behind the idea. Concomitantly, it seeks to identify the variations in the importance accorded by different investors to the several variables of the EBPE model, and whether these variations-and also the stages of business-influence the final investment decisions of investors. The findings of this mixed methods study hold significant implications for various stakeholders, and suggest that the presence of the EPBE model's dimensions in an entrepreneur are very necessary for attracting investors' capital. The personal branding of the A-team in particular, clearly emerged as the most critical variable of the EBPE model, based on the type of investor and stage of the entrepreneurial venture.